PHASE-STABILITY OF TERNARY BLENDS - KIM, CK; KIM, JJ; PAUL, DR (WILEY-BLACKWELL, 1994)
The phase behavior of ternary blends of tetramethyl polycarbonate (TMPC), polycarbonate (PC), and styrenic polymers has been examined by experiment and analyzed in terms of thermodynamic theories. The phase boundaries were predicted using both the modified Flory-Huggins theory and the lattice fluid theory. The boundaries predicted using the lattice fluid theory agree best with the experimental results. The experimental phase behavior of ternary blends was compared with binary blends having exactly the same chemical components and compositions except that the TMPC and PC units were present in the form of a copolycarbonate in the binary. The miscible region of these ternary blends is much narrower than that of the corresponding binary blends, even though the entropic and energetic terms of such ternary blends are more favorable than those of the binary blends. It is shown that a negative value of noncombinatorial free energy in multicomponent systems is not a sufficient condition for miscibility, because of asymmetries of mer-mer interactions. A comparison of the stability conditions for these binary and ternary blends shows that increasing the degrees of freedom tends to destabilize the mixture.
Keywords: BISPHENOL-A POLYCARBONATE; POLY(METHYL METHACRYLATE); POLYMER BLENDS; INTERACTION PARAMETERS; POLY(2,6-DIMETHYL-1,4-PHENYLENE OXIDE); LIGHT-SCATTERING; CO-POLYMERS; COPOLYMERS; MISCIBILITY; BEHAVIOR